Implementation of Life Cycle Assessment (LCA) and Life Cycle Cost Life (LCC) on Particle Board Wood Furniture Industry in Yogyakarta - Erza Drajat Prabowo; Tatbita Titin Suhariyanto (OPSI, 2021)
CV. Limase Laras is a wood furniture industry in Yogyakarta that has increased production. The company uses electrical energy which contributes to carbon dioxide (CO2) emissions and produces solid waste of sawdust in the production process. On the other hand, with the large assets and high sales of the company, it is important to conduct financial analysis thus the company does not make wrong decisions. Based on these problems, the methods used in this study are Life Cycle Assessment (LCA) to evaluate environmental impacts and Life Cycle Cost (LCC) to analyze life cycle costs. From the LCA analysis, sawdust waste is the highest impact by producing four environmental impacts, namely, global warming (936 x 10-2 kg CO2-eq), aquatic eutrophication (2.12 x 10-3 kg NO3-eq), photochemical ozone formation that affects humans (9.04 x 10-3 person*ppm*hours), and photochemical ozone formation that affects plants (113 m2 UES). From the LCC analysis, the NPV value is Rp8,278,512,276.00, which means that the bookshelf production process provides benefits for the company. The B/Cnet value is 37.9, which means that the bookshelf is beneficial. However, the bookshelf production process will be not feasible to continue if the company experiences a 40% decrease in annual revenue.